Digitalization of HR Roles in Retail Companies: A Conceptual Model - Bagas Taqwa (PT. Berkah Digital Teknologi, 2025)
Purpose: This conceptual study aims to explore the impact of digitalization on the role of Human Resources (HR) in retail companies. It specifically investigates how digital tools such as HR analytics and automation are transforming HR from a transactional function into a strategic partner. Research Methodology: This research utilizes a thematic literature review approach, synthesizing 27 studies from Scopus, Google Scholar, and other databases published between 2010 and 2024. The review integrates the Dynamic Capability Theory and Strategic Human Resource Management (SHRM) to construct a theoretical framework. Results: The findings indicate that digitalization significantly drives the automation of HR processes, the adoption of HR analytics, and the need for new competencies. As a result, HR's role is evolving from administrative tasks to strategic decision-making, positioning HR as a key enabler of organizational agility and innovation. Limitations: This study is conceptual in nature and does not include empirical data. Additionally, it focuses primarily on medium-to-large retail companies and does not address small and medium-sized enterprises (SMEs) in retail. Contribution: This paper contributes to the HR literature by developing a conceptual model that illustrates the transformation of HR roles in retail businesses through digitalization. It also provides theoretical propositions for future research and practical recommendations for HR practitioners in the retail sector.